An Empirical Study on The Default Risk of Kaisa' s Real Estate Industry Before and After COVID-19 - Huang, Yi (BCP Business & Management, 2022)
In 2019, when COVID-19 outbroke, the real estate economy, an important component of the economy, must be hit to some extent. Affected by the epidemic and financing situation, Kaisa enterprise recently suffered a credit risk. The debt was increasing and the credit ratings were decreasing. The stock of Kaisa was suspended for a long time. This paper used the financial data of Kaisa enterprise between 2019 and 2021 provided by Eastern Wealth and the financial statements of Kaisa enterprise to measure the credit risk of Kaisa enterprise with the KMV model. The empirical results illustrated that the default probability of Kaisa enterprise was relatively high and the default probability increases to some extent after the outbroke of the COVID-19 epidemic. Between 2020 and 2021, Kaisa enterprise was classified as CCC credit rate according to the Standard & Poor's credit rating table. The data and standard confirmed Kaisa enterprise had a high credit risk. To resolve and prevent credit risks, Kaisa enterprise needs to improve the liquidity of funds, carry out reasonable financing and improve the awareness of risk management.